Implementation of Differentiated Learning to Improve the Quality of Learning - Hastutik, Sri; Masduki, Masduki (Jurnal Ilmiah Iqra', 2024)
The need for differentiated learning is very urgent because students have various abilities. Therefore, the quality of learning can be improved by implementing differentiated learning. This research is a field research with a qualitative approach with a case study type. Data collection techniques use in-depth interviews, participant observation, and documentation studies. Data analysis used is the Miles, Huberman and Saldana model. The results of this study are: Educators in MI Plus al-Istighotsah Panggungrejo carry out differentiated learning as an implementation of the independent curriculum. In differentiating learning in MI Plus al-Istighotsah Panggungrejo is carried out with modification and innovation even though it is a method of modification of the method of combining several learning methods so that they are able to understand students and also modification of learning media using varied learning media so as to reduce the boredom of students. Learning that varies and innovatively is able to increase student motivation as evidenced by the growth of students' enthusiasm to participate in learning in the classroom and even the growth of achievement motivation in students. Increasing students' motivation to learn will increase students' achievement, as proven by the increase in final semester grades in several subjects where differentiated learning was implemented. Learning that is differentiated can improve the quality of the learning process because the indicators of learning quality are fulfilled as a whole.